A relevância do periodontista na prevenção da doença periodontal em pacientes ortodônticos: relato de caso clínico - Ferreira, Jean Paulo Rodolfo [UNESP]; Araújo, Paula Caetano [UNESP]; Saliba, Marcos Tadeu Adas [UNESP]; Garbin, Cléa Adas Saliba [UNESP] (My University, 2011)
The increase of the retentive areas of bacterial plaque can be observed in patients who use dental braces in the mouth. The difficulty of making hygienic is one of the problems that this particular group of patients faces day by day, and consequently, the establishment of gingival inflammation becomes more frequent. The objective of this case report is to show the importance of the periodontist in preventing and promoting health to the users of dental braces, aimed at education and motivation as one of the priorities of this treatment. The ESA patient, 29 years old, male, attended the dental office of a periodontist, sent by the orthodontist, due to the extensive area of gingival hyperplasia and gingivitis, in both arches. The possibility of taking out the dental braces was considered by the orthodontist, but after the periodontist evaluation, this step was procrastinated. Thus, the periodontist started the adequacy of the oral environment together with the work of education and promotion of health, which lasted until the complete recovery of the healthy gingival condition of the patient. In this way, it is possible to observe the relevance of the work of the periodontist in the application of preventive methods in oral health for orthodontic patients. The motivation of these patients in relation to the orientations of buccal hygienic, maintenance of oral health and diet should not be considered as secondary and should be prioritized, because only in this way it would be possible to reach a good occlusion, without esthetic and functional prejudice.

O aumento das áreas retentivas de placa bacteriana, pode ser observado em pacientes que fazem uso de aparelhos fixos na boca. A dificuldade de higienização é um dos problemas que este grupo específico de pacientes enfrenta no cotidiano, e conseqüentemente, a instalação de inflamações gengivais se torna mais freqüente. O objetivo deste relato de caso clínico é mostrar a importância do periodontista na prevenção e na promoção em saúde dos usuários de aparelho fixo, visando à educação e a motivação como uma das prioridades dentro deste tratamento. O paciente E.S.A., 29 anos, sexo masculino, compareceu ao consultório odontológico de um periodontista, encaminhado pelo ortodontista, devido à extensa área de hiperplasia gengival e gengivite, nos dois arcos dentários. A hipótese de retirada da aparelhagem foi considerada pelo ortodontista, porém após avaliação do periodontista, esta medida foi procrastinada. Sendo assim, o periodontista iniciou uma adequação do meio bucal em conjunto com o trabalho de educação e promoção em saúde, que se estendeu até o total restabelecimento da condição gengival saudável do paciente. Desta maneira, pode-se observar a relevância da atuação do periodontista na aplicação de métodos preventivos em saúde bucal à pacientes ortodônticos. A motivação destes últimos em relação às orientações de higienização, manutenção da saúde bucal e dieta alimentar devem deixar de ser consideradas secundárias e ser priorizadas, pois só assim será possível alcançar uma boa oclusão, sem prejuízo estético e funcional.
The relevance of the periodontist in the prevention of periodontal disease in orthodontic patients: case report
Keywords: Gingival diseases - prevention and control; Periodontics; Doenças da gengiva - prevenção e controle; Periodontia